2015
DOI: 10.1021/ac503813r
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Transport Selectivity of Ionic Species by Phosphoric Acid Gradient in Positively Charged Nanochannel Membranes

Abstract: The transport of ionic species through a nanochannel plays important roles in fundamental research and practical applications of the nanofluidic device. Here, we demonstrated that ionic transport selectivity of a positively charged nanochannel membrane can be tuned under a phosphoric acid gradient. When phosphoric acid solution and analyte solution were connected by the positively charged nanochannel membrane, the faster-moving analyte through the positively charged nanochannel membrane was the positively char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…16f). With the same anion in the draw solution (Cl − ), this order was consistent with the increase in cationic radius, i.e., K + (0.331 nm) < Na + (0.358 nm) < Ca 2+ (0.412 nm) < Cu 2+ (0.419 nm) < Mg 2+ (0.428 nm), and thus attributed to a slower transfer rate for larger cations across the membrane 47,48 . This osmotic pressure-driven permeation allowed the PTL membrane to be operated in an FO mode with low energy consumption and fouling propensity compared to reverse osmosis membrane technology 13,45 .…”
Section: Resultssupporting
confidence: 65%
“…16f). With the same anion in the draw solution (Cl − ), this order was consistent with the increase in cationic radius, i.e., K + (0.331 nm) < Na + (0.358 nm) < Ca 2+ (0.412 nm) < Cu 2+ (0.419 nm) < Mg 2+ (0.428 nm), and thus attributed to a slower transfer rate for larger cations across the membrane 47,48 . This osmotic pressure-driven permeation allowed the PTL membrane to be operated in an FO mode with low energy consumption and fouling propensity compared to reverse osmosis membrane technology 13,45 .…”
Section: Resultssupporting
confidence: 65%
“…Recently by imposing different concentrations of salt to the two ends of charged nanochannels, a bunch of interesting transport phenomena have been reported. As shown in Figure b, due to the larger concentration C max in the left chamber ( z < − L /2) the counterions at that end of the channel are more densely piled up, while at the opposite C min end the layer of screening ions is much thicker. Hence a nonuniformity of ion distribution along the channel axis arises.…”
mentioning
confidence: 99%
“…However, the experiments showed much more complicated behaviors. ,, One central discovery is the transition of fluidics from osmosis to the reverse one with increasing salt gradient. Yang et al , showed a four-stage variation of EOF: at first an osmotic flow was boosted given small LiCl concentration bias C max / C min across the channel (region I in Figure b); as the imposed salt gradient was enhanced, the osmotic flow first increased and then switched to decrease (region II in Figure b); when the salt gradient became larger than a critical value, the fluidics shifted to reverse osmosis (RO, region III in Figure b); if the salt gradient still kept increasing, once again the magnitude of RO began to decrease (region IV in Figure b) In summary, rather than monotonic increasing there existed a transition of osmotic flow to the reversed one. Furthermore, within either osmosis or reverse osmosis there was U-turn-like dependence of the fluidics on the imposed salt gradient.…”
mentioning
confidence: 99%
“…However, the dehydration effect governs the ionic trans port in a low number of negatively surface charges, and thereby nanochannel affinity switched to Li + ions at small surface charge densities. [204] Razmjou and et al fabricated an efficient 2D negatively charged vermiculite (VCT)based nanochannel for separation of Li + ions in aquatic environments. The sche matic and microscopy images of fabricated VCT nanosheets are displayed in Figure 6Aa,b.…”
Section: Charge-based Selectivitymentioning
confidence: 99%